PRAKTIK GEOWISATA KARANGSAMBUNG KEBUMEN: TINJAUAN PERSPEKTIF DUALITAS - Nugroho, Saptono (Jurnal Master Pariwisata (JUMPA); Volume 03, Nomor 01, Juli 2016, 2016)
This research aims to understand the practice of geotourism in the area of Karangsambung Geological Nature Reserve, Central Java, with the perspective of duality as a tool of analysis.It was designed by qualitative methods, which was suitable to be applied to understand the dynamics of the uniqueness of human behavior that occurs naturally.The research finding are, the practice of geotourism in Karangsambung which is produced by the Center for Information and Terrestrial Conservation Indonesian Institute of Sciences (BIKK - LIPI) Karangsambung is still caught in the trap of dualism perspective.Geotourism practice which managed exclusively by BIKK – LIPI, it becomes a device for the continuity of symbolic violence against local people.It is a tourism-based violence. It needs the effort to create a new tourism structure that can accommodate the aspirations of the actors in Karangsambung, using panginyongan strategy to break the chain of dualism into duality perspective.
Keywords: geotourism practice, duality perspective, tourismbased violence, panginyongan strategy.